2001
DOI: 10.1590/s0100-879x2001000600014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lead and/or zinc exposure during the second stage of rapid postnatal brain growth on delta-aminolevulinate dehydratase and negative geotaxis of suckling rats

Abstract: Lead has been shown to produce cognitive and motor deficits in young rats that could be mediated, at least in part, by inhibition of the zinccontaining heme biosynthetic enzyme d-aminolevulinate dehydratase (ALA-D). In the present study we investigated the effects of lead and/ or zinc treatment during the second stage of rapid postnatal brain development on brain, kidney and blood ALA-D specific activity, as well as the negative geotaxis behavior of rats. Eight-day-old Wistar rats were injected intraperitoneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…[95][96][97] The stimulation of δ-ALA-D synthesis after Pb(II) intoxication was interpreted as a compensatory response to the enzyme inhibition. We have observed that a short-term exposure of suckling rats to high doses of Pb(II) caused an increase in blood δ-ALA-D activity 35 and an increase in the reactivation index by dithiothreitol (DTT) + Zn(II) of two times, 98 corroborating the findings of Fujita and collaborators. [95][96][97] In contrast to rats, workers from battery manufacturing plants exposed to lead exhibited an increase in δ-ALA-D gene methylation and a decrease in δ-ALA-D transcription.…”
Section: Pb(ii) In Vivosupporting
confidence: 88%
“…[95][96][97] The stimulation of δ-ALA-D synthesis after Pb(II) intoxication was interpreted as a compensatory response to the enzyme inhibition. We have observed that a short-term exposure of suckling rats to high doses of Pb(II) caused an increase in blood δ-ALA-D activity 35 and an increase in the reactivation index by dithiothreitol (DTT) + Zn(II) of two times, 98 corroborating the findings of Fujita and collaborators. [95][96][97] In contrast to rats, workers from battery manufacturing plants exposed to lead exhibited an increase in δ-ALA-D gene methylation and a decrease in δ-ALA-D transcription.…”
Section: Pb(ii) In Vivosupporting
confidence: 88%
“…These results are in accordance with several preceding studies [9,37,48,72,73] that reported similar findings of neuronal degeneration in Pb and other heavy metal toxicity on the cerebellums, with more consequences for the Purkinje cells due to sensitivity of the Purkinje cell layer. Further, previous studies also documented the toxic effect of Pb administration on juvenile and young rats, resulting in different neurological impairments in various parts of the brain and nervous system [74,75,76,77]. However, treatment with curcumin reversed the above-mentioned Pb-induced morphological aberrations in the rats.…”
Section: Discussionmentioning
confidence: 92%
“…Test pups were placed head down on the rough surface and allowed to turn 180° within 60 s [9] . The pups were tested for negative geotaxis on days 8, 10 and 12 of age.…”
Section: Negative Geotaxismentioning
confidence: 99%